2022
DOI: 10.1177/15347354221105485
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Egg Are Risk Factors for Adverse Effects of Capecitabine-Based Chemotherapy in Chinese Colorectal Cancer Patients

Abstract: Background: Chemotherapy-induced adverse effects (CIAEs) remain a challenging problem due to their high incidences and negative impacts on treatment in Chinese colorectal cancer (CRC) patients. We aimed to identify risk factors and predictive markers for CIAEs using food/nutrition data in CRC patients receiving post-operative capecitabine-based chemotherapy. Methods: Food/nutrition data from 130 Chinese CRC patients were analyzed. Univariate and multivariate analyses were used to identify CIAE-related food/nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…A previous study showed that a person with a high SM (d40:2) level had a lower risk of getting chronic kidney disease . Similarly, a study has indicated that nut consumption may be beneficial for colorectal cancer patients and is positively correlated with SM (d40:2) levels in plasma . However, it remains unclear whether direct intake of SM (d40:2) has any beneficial effects on human kidney or gut health, and further investigation is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that a person with a high SM (d40:2) level had a lower risk of getting chronic kidney disease . Similarly, a study has indicated that nut consumption may be beneficial for colorectal cancer patients and is positively correlated with SM (d40:2) levels in plasma . However, it remains unclear whether direct intake of SM (d40:2) has any beneficial effects on human kidney or gut health, and further investigation is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…59 Similarly, a study has indicated that nut consumption may be beneficial for colorectal cancer patients and is positively correlated with SM (d40:2) levels in plasma. 60 However, it remains unclear whether direct intake of SM (d40:2) has any beneficial effects on human kidney or gut health, and further investigation is necessary. The overlap between significantly different lipid species in each comparison group is shown using a Venn diagram (Figure S5a).…”
Section: Ether Plmentioning
confidence: 99%
“…Last but not least, screening miRNAs from normal tissues other than tumors may provide more informative clues. Accumulating evidence suggests that the efficacy and safety of chemotherapy are not solely dependent on drug metabolism but also on the overall physiological functions [44,[48][49][50][51][52][53]. Individual differences in cell maintenance, proliferation, and immune function also influence the response to chemotherapy.…”
mentioning
confidence: 99%